A new species of the genus Xenylla Tullberg, 1869 (Collembola: Hypogastruridae) from Korea, with a key for East Asian species - Park, Kyung-Hwa (Zootaxa, 2016)
A new species of Hypogastruridae from Korea, Xenylla namia sp. nov., is described and illustrated. The new species is easily distinguished from previously described Xenylla species by a combination of the following characters: labral setae arrangement of 2/5,5,4, labial papilla E with one guard seta (e3), head without c2 seta, thoracic sterna II and III with a pair of medial setae, abdominal sternum III with 1 median seta above the retinaculum, abdominal sternum IV with seta m1. An identification key to East Asian species of Xenylla with detailed differences between East Asian Xenylla species is provided.